Mathematical Support of Crisis Planning - Milata, I.; Rostekova, Lenka; Kaspar, Vladislav; Dvorak, Zdenek (Communications - Scientific letters of the University of Zilina, 2005)
It is impossible to eliminate the occurrence of crises and crises situations in society, nature and in production processes. That is why it is necessary to search for such paths and procedures, which would minimise the crises processes and consequences. Methods of mathematical statistics provide valuable information for crises planning in the sphere of mathematical forecasting.